MANAJEMEN PERPUSTAKAAN SEKOLAH/MADRASAH - Anis Zohriah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2018)
Corresponding with recent developments lately, libraries need to be understood not just as institutions that manage books and other publications, but also manage information resources by utilizing information technology. Therefore, needed power of master to have personnel who dominate expertise and skills in certain fields. To manage the school library, a teacher who is considered capable of managing the library should be appointed. Management in the school library is not just an activity of placing books on a shelf, but more than that, it is very complex, sustainable, and always changing. So management is a process that focuses on attention to activities from day to day, facing problems with content and integration with school goals. Keywords. Management, school library